Repairing political trust for practical sustainability - Weymouth, Robert; Hartz-Karp, Janette; Marinova, Dora (MDPI AG, 2020)
High levels of trust in government are important in addressing complex issues, including the realization of the mainstream sustainability agenda. However, trust in government has been declining for decades across the western world, undermining legitimacy and hampering policy implementation and planning for long-term sustainability. We hypothesize that an important factor in this decline is citizen disappointment with the current types of public participation in governance and that this could be reversed through a change from informing/consulting to a relationship of partnership. Using case studies from Western Australia, the paper investigates whether an intervention targeted at establishing a partnership relationship through mini-public, deliberative, participatory budgeting would improve trust and help the implementation of sustainability. These results show evidence of improvements in trust and provide conceptual and practical tools for government administrations wishing to close the detrimental trust gap that may hamper the implementation of a sustainability agenda.